Perceived Behavioral Control and Intention Related to The Smoking Behavior of Early Adolescents in North Surabaya - Lisa Setyowati; Ika Yuni Widyawati; Sylvia Dwi Wahyuni (Jurnal Ners, 2020)
Introduction: Smoking behavior in adolescents is a phenomenon that should be considered and can be easily found nowadays. The prevalence of teenage smokers aged 10-18 years in Indonesia increases every year. Smoking behavior can have various negative impacts both in terms of health, but also economic, social and psychological. The purpose of this research was to analyze factors related to smoking behavior in adolescents.Methods: A descriptive analysis with a cross-sectional approach was used in this research. 96 early adolescents participated in this research who were selected using a purposive sampling technique. The data was obtained from Belief-based Tobacco Smoking Scale questionnaires then analyzed using regression statistical tests (α<0.05).Results: The results showed that perceived behavioral control and intention are significantly related to the smoking behavior of early adolescents in North Surabaya. The most influencing factor is perceived behavioral control. Weak perceived behavioral control by parents and strong intentions in adolescents to smoke the following month affect the behavior of early adolescents in North Surabaya to smoke.Conclusion: This finding can be used as one of the topics that need to be considered in improving community nursing services in the prevention of smoking phenomena in adolescents by providing adequate information through counseling about smoking cessation and treatment efforts that can be done.